Indonesian EFL Learners' Refusal: Refusal-Speech Act Specific Motivation on Refusal Realization - Dwiana, Nadya Rezkhita; Syahri, Indawan (Indonesian Journal of EFL and Linguistics, 2024)
Knowing how to produce speech act especially refusal appropriately is necessary since it is known as ‘face-threatening’ act, otherwise it would lead to discomfort between interlocutors. This ability may be influenced by many factors, one of which is motivation. One of the pragmatic motivation types is Speech Act Specific Motivation (SASM), which was found to have explanatory power to predict production of a certain speech act. This study aimed to investigate the correlation between learners’ refusal-SASM and their refusal. The subject was the students of English Education Program of Universitas Muhammadiyah Palembang. Discourse Completion Task (DCT) and refusal-SASM questionnaire were used in collecting the data needed. The results showed that the correlation between the two variables was insignificant, the refusal-SASM contributed only 3% towards the learners’ refusal. The recent study also found that the leaners tended to use indirect strategy in refusing to almost all situations. The reason of this phenomenon is likely to be the influence of L1 culture. However, further studies are highly suggested in this matter.